Educação como requisito na Escola de Futebol Bom de amigo bom de bola no município de Brejinho de Nazaré-TO - Menezes, Janaína dos Santos (Universidade Federal do Tocantins, 2023)
The objective of this work is to carry out a study directed to Associação Beneficente Nestorina Ana Ferreira, in the municipality of Brejinho de Nazaré, analyzing the importance of education as a requirement for permanence in the Football School that integrates the Association. The objectives of this work were: To know the socioeconomic profile of the members, to identify the criteria for permanence of the students who are 7 to 17 years old in the soccer school, which are approximately 100 children, to analyze the contributions of the Association to society and to point out the importance of teaching in the training process of the members. The purpose of this research is to contribute by showing the actions of the Association and the importance of education as a requirement for permanence in the Football School that integrates the entity. After an interview and application of the questionnaires on September 28, 2021. We then tabulated the questions and had as answers that the work done at the Association is of paramount importance, since most of those questioned report that their children were better at school, at home, for example: in behavior and dedication to studies. We can see that the Association is doing a very important job for the community that goes far beyond a football game. They are prepared to be better people in a society that is very unbalanced because they are the future generation.